The Effect of Blended Learning by Means of Assisting in The Development of Some Motor Abilities and Learning the Skills of The Blocking Wall and Defensive Moves In The Handball By Females’ Students - Turki Hashim, Zaman; Abdel Karim, Ahmed Kazem; Al-Jubouri, Ayman Hani Abd (International Journal of Psychosocial Rehabilitation, 2020)
1- Preparing an educational curriculum for blended learning by means of assisting in developing some motor abilities and learning the skills of the blocking wall and defensive moves in the handball sport for students. 2- Knowing the effect of blended learning by means of assisting in developing some motor abilities and learning the skills of the blocking wall and defensive moves in the handball sport for students The researchers used the experimental approach, as the research community was determined the second stage students in the College of Education for Girls, Department of Physical Education and Sports Science, who are (30) students, then, the educational curriculum was applied to a sample of the community which is about (20) students, then the appropriate statistical treatments were used to arrive at the results, after which the results were presented, analyzed and discussed. The researchers have reached to the following conclusions: 1. Using the blended learning has a positive effect in developing some kinetic abilities, accuracy of the blocking wall and defensive moves of students with handball. 2. The use of educational assistant is better than the method, which is used, that increased the effectiveness of learning the skills of the barrier and defensive moves in the game of handball. 3. Blended learning by using educational methods has had an effect in learning the accurate performance of defensive skills, movements and in the correct form. Basing on the results of the research, the researchers has reached the most important following recommendations: 1. Adopting a blended learning approach by using educational methods in the process of learning handball skills as well as the possibility of using it for students of colleges of physical education and sports science and its departments. 2. Educational means should be an essential part of the content of the educational curriculum for basic skills in handball. 3. Emphasis on generalizing the contents of (blended learning and educational means) in learning handball and benefiting from the experiences which it provides in the educational process.